White blood cell and platelet count as adjuncts to standard clinicalevaluation for risk assessment in patients at low probability of acute aorticsyndrome. Issue 5 (1st August 2017) - Morello, Fulvio; Cavalot, Giulia; Giachino, Francesca; Tizzani, Maria; Nazerian, Peiman; Carbone, Federica; Pivetta, Emanuele; Mengozzi, Giulio; Moiraghi, Corrado; Lupia, Enrico
Abstract: Aims: Pre-test probability assessment is key in the approach to suspected acuteaortic syndromes (AASs). However, most patients with AAS-compatible symptomsare classified at low probability, warranting further evaluation fordecision on aortic imaging. White blood cell count, platelet count andfibrinogen explore pathophysiological pathways mobilized in AASs and areroutinely assayed in the workup of AASs. However, the diagnostic performanceof these variables for AASs, alone and as a bundle, is unknown. We testedthe hypothesis that white blood cell count, platelet count and/or fibrinogenat presentation may be applied as additional tools to standard clinicalevaluation for pre-test risk assessment in patients at low probability ofAAS. Methods and results: This was a retrospective observational study conducted on consecutivepatients managed in our Emergency Department from 2009 to 2014 for suspectedAAS. White blood cell count, platelet count and fibrinogen were assayedduring evaluation in the Emergency Department. The final diagnosis wasobtained by computed tomography angiography. The pre-test probability of AASwas defined according to guidelines. Of 1210 patients with suspected AAS, 1006 (83.1%) were classified at low probability, and 271 (22.4%) werediagnosed with AAS. Within patients at low probability, presence of at leastone alteration among white blood cell count >9*10 3 /µl, platelet count <200*10 3 /µl and fibrinogen <350 mg/dl wasassociated with a sensitivity of 95.5% (89.7–98.5%) and a specificity of18.3% (15.6–21.2%). In patients at low probability, white blood cell count>9*10 3 /µl and platelet count <200*10 3 /µlwere found as independent predictors of AAS beyond established clinical riskmarkers. Within patients at low probability, the estimated risk of AAS basedon the number of alterations amongst white blood cell count>9*10 3 /µl and platelet count <200*10 3 /µl was2.7% (1.2–5.7%) with zero alterations, 11.3% (8.8–14.3%) with one alterationand 31.9% (24.8–40%) with two alterations ( p <0.001). Conclusion: In addition to standard clinical evaluation, white blood cell count andplatelet count may be used in patients at low pre-test probability tofine-tune risk assessment of AAS.